Evaluation of the Chemical Quality of Based Rations Guinea Grass (Panicum maximum) through Combination of Different Swamp Forages - Riswandi Riswandi; Muhakka Muhakka; Agus Wijaya; Afnur Imsya; Desi Kurnia; Cempaka Kirana (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
Swamp forage has the potential as an alternative feed for ruminants. This study aimed to evaluate the chemical quality of Guinea grass (Panicum maximum) based rations through a combination of different types of swamp forage. This research was conducted for 3 months at the Animal Feed Nutrition Laboratory, Faculty of Agriculture, Sriwijaya University. The design used in this study was a completely randomized design (CRD) consisting of 4 treatments and 4 replications. The treatments consisted of R0 (70% Guinea grass + 30% Concentrate), R1 (40% Guinea grass + 30% water mimosa + 30% Concentrate), R2 (40% Guinea grass + 30% giant molesta + 30% Concentrate), R3 (40% Guinea grass + 30% water chestnut + 30% Concentrate). The variables observed were dry matter (DM), organic matter (OM), crude protein (CP), crude fiber (CF), extract ether (EE), tannin and saponins. The results showed that the treatment had a significant effect (P < 0.05) on the content of DM, OM, CP, CF, Tannins and Saponins, while the extract ether content had no significant effect (P > 0.05). Furthermore, highest DM (82.45%), OM (76.96%) and CP (16.35% were obtained in R1, CF (22.34%) in R0. Tannin best concentration (1.09%) in R3 and saponins (2.16%) in R1. The conclusion of this study showed that the combination of 40% Guinea grass + 30% water mimosa + 30% concentrate could improve the chemical quality of the ration.